The Influence Of Career Development On Employee Retention With Job Satisfaction As An Intervening Variable PT. Socfindo Tanah Besih - Febri Andriyani; Nurul Aida; Mangasi Sinurat; Cia Cai Cen (SEAN Institute, 2024)
The study's overarching goal is to identify how PT. Socfindo Tanah Besih's career development programs affect staff retention rates, with work satisfaction serving as a moderating variable. Campany's capacity to maintain high personnel retention is the driving force behind the company's growth. In this quantitative study, 57 participants were selected at random from among the staff of PT. Socfindo Tanah Besi. Validity, reliability, normalcy, multicoliniearity, and heteroskedasticity are the analytical criteria used in this study. This study used SPSS version 25 for data processing and hypothesis testing, which included a t-test, determinant coefficient, and path analysis. Testing the hypotheses reveals that career development has a substantial impact on work satisfaction, but neither career development nor job satisfaction has any bearing on employee retention, and neither factor can mediate the link between the two.